A soft X‐ray free‐electron laser beamline at SACLA: the light source, photon beamline and experimental station. (12th December 2017) - Owada, Shigeki; Togawa, Kazuaki; Inagaki, Takahiro; Hara, Toru; Tanaka, Takashi; Joti, Yasumasa; Koyama, Takahisa; Nakajima, Kyo; Ohashi, Haruhiko; Senba, Yasunori; Togashi, Tadashi; Tono, Kensuke; et al.
Abstract : The status of a soft X‐ray free‐electron laser beamline at SACLA is reported. Abstract : The design and performance of a soft X‐ray free‐electron laser (FEL) beamline of the SPring‐8 Compact free‐electron LAser (SACLA) are described. The SPring‐8 Compact SASE Source test accelerator, a prototype machine of SACLA, was relocated to the SACLA undulator hall for dedicated use for the soft X‐ray FEL beamline. Since the accelerator is operated independently of the SACLA main linac that drives the two hard X‐ray beamlines, it is possible to produce both soft and hard X‐ray FEL simultaneously. The FEL pulse energy reached 110 µJ at a wavelength of 12.4 nm ( i.e. photon energy of 100 eV) with an electron beam energy of 780 MeV.